Role of crumb tyre aggregates in rubberised concrete contained granulated blast-furnace slag. (January 2019) - Mhaya, A M; Abidin, A R Z; Sarbini, N N; Ismail, M
Abstract: Wise management of waste materials can be quite intensive in terms of ecological friendliness and human safety. Proper recycling of industrial wastes can lead to immense practical benefits. This paper determines the feasibility of improving the properties of concrete by incorporating waste tyre aggregates (TAs) and ground granulated blast-furnace slag (GGBFS) at varied percentages. Construction applications of rubberised concrete (RC) is limited due to presence of weak bonds between the cement paste and rubber lumps. The size and hardness of the rubber aggregates in RC make its compressive strength lower compared to traditional one. To overcome such shortcomings, GGBFS was included. Furthermore, crumb TAs of two different size distributions (fine lumps of size range 1 to 4 mm and coarse piles of sizes within 5 to 8 mm) at varied levels (5, 10, 20 and 30% of volume) were used to replace GGBFS addition to concrete. Three groups of concrete specimens were prepared, first group using TAs (size 1 to 4 mm) as partially replaced fine aggregates, second group using TAs (size 5 to 8 mm) as partly replaced coarse aggregates and the last group partially replaced both TAs. Next, GGBFS of 20% as partial replacement of cement was admixed to all groups and compared with the control mix. Workability and mechanical properties of the designed mixes were evaluated in terms of slump and compacting factor, compressive, flexural and tensile strengths, and modulus of elasticity. Specimens containing GGBFS revealed improved mechanical behaviour. Meanwhile, the compressive strength of OPC specimen (after 3 months of curing) was 37.17 MPa. Moreover, specimen mixed with 5% of TA as replacement of coarse aggregates and 20% of GGBFS was almost 6% higher than the OPC specimens (39.54 MPa). It was concluded that recycled TAs as waste material could potentially be combined with GGBFS to attain high strength RC, constituting a novel strategy with immeasurable environmental, technological and economic benefits.